Farm fresh food boxes: Increasing food access in rural communities and urban food deserts through new markets for farmers and retailers - Diane Smith (Urban Food Systems Symposium, 2020)
Farm Fresh Food Boxes (F3B) is a multi-state integrated research and extension project that represents an innovative approach to addressing access to healthy, affordable food in food deserts by connecting farmers, retailers, and consumers. The extension team was responsible for recruiting farms and associated retail sites in three participating states: Vermont, Washington, and California, and promoting this innovative program to consumers in communities with limited access to fresh, local produce. The research team conducted mixed-methods research on the experience of participating F3B farmers, retailers, and consumers. Farms offered weekly boxes of fresh produce at retail sites that provide convenient access to consumers. Retail sites advertised with flyers detailing the weekly content and cost of F3B from participating area farms. Customers’ pre-purchased boxes at the retail site or online on a week-to-week basis for later pick-up. Box contents and flyers change throughout the season to reflect seasonal availability and to move produce that is most abundant. Findings from mixed methods data collection include an assessment of market potential, revenue from box sales, measures of acceptability, and benefits and barriers to farmers, retailers, and consumers. F3B provides a low-risk strategy to address the complex supply, demand, and distribution challenges faced by producers and retailers of fresh local foods, while overcoming barriers that consumers face in accessing affordable, healthy food.
Keywords: alternative food network; community supported agriculture (CSA); local foods; values-based supply chain; direct to consumer (DTC)